Rancang Bangun Electronic Load Control Generator pada Pembangkit Listrik Tenaga Mikro Hidro Berbasis Mikrokontroler dan IoT - sofyan, sofyan; Naim, Kurniawati; Basri, Muh Arga (Jurusan Teknik Elektro Politeknik Negeri Ujung Pandang, 2022)
Changes in frequency and voltage caused by erratic load changes on consumers of Micro Hydro Power Plants (MHP) can damage generators and household appliances consumers. This problem can be addressed by providing a replacement load. However, to optimize the replacement load, it is necessary to design a control system for the replacement load. This research was conducted to control the generator output when an erratic load change occurs. In addition, this study also aims to monitor the generator output remotely using the internet. Accordingly, the research was conducted with hardware design and software design. Data collection is done by testing technique, while data analysis is done by simple regression. Based on the results of research and discussion, it can be concluded that the use of design tools can control the replacement load and measure voltage, current, and frequency. The use of this tool can also monitor and store data using the GSM internet network so that monitoring can be carried out remotely